Online Brazilian Journal of Nursing has a new site and a new way of management - Cruz, Isabel Cristina Fonseca da (Online Brazilian Journal of Nursing, 2005)
The OBJN joined to the Public Knowledge Project. Now, the OBJN utilizes the Open Journal Systems(OJS) software, a journal management and publishing system. The OJS helps the OBJN ́s editor from managing submission reviews through to online publication and indexing. It was possible because the OJS is made freely available to open access research journals. The OBJN believes that open access publishing at the WWW can increase a journal's readership as well as its contribution to the public good on a global scale. It is important to point out that in Brazil the OJS was translated and adapted by the IBICT. The OJS become the Sistema Eletrônico de Editoração de Revistas (SEER). The new OBJN with the OJS or SEER management system is very simple for the journal editors, authors, reviewers or management staff. What will change now a days?